Determinants of Inappropriate Antibiotics Use in Rural Central Ghana Using a Mixed Methods Approach - Afari-Asiedu, Samuel; Oppong, Felix Boakye; Tostmann, Alma; Ali Abdulai, Martha; Boamah-Kaali, Ellen; Gyaase, Stephaney; Agyei, Oscar; Kinsman, John; Hulscher, Marlies; Wertheim, Heiman F. L.; Asante, Kwaku Poku (Frontiers in Public Health, 2020)
Background: The consequences of antibiotic resistance are projected to be most severe in low and middle income countries with high infectious disease burden. This study examined determinants of inappropriate antibiotic use at the community level in rural Ghana. Methods: An observational study involving qualitative and quantitative methods was conducted between July, 2016 and September, 2018 in Ghana. Two household surveys were conducted at two time points (2017 and 2018) among 1,100 randomly selected households over 1 year. The surveys focused on antibiotic use episodes in the past month. Four in-depth interviews and two focus group discussions were performed to further explain the survey results. Determinants of inappropriate antibiotic use were assessed using a mixed effect logistic regression analysis (multilevel analysis) to account for the clustered nature of data. We defined inappropriate antibiotic use as either use without prescription, not completing treatment course or non-adherence to instruction for use. Qualitative data were thematically analyzed. Results: A total of 1,100 households was enrolled in which antibiotics were used in 585 (53.2%) households in the month prior to the surveys. A total of 676 (21.2%) participants out of 3,193 members from the 585 reportedly used antibiotics for 761 episodes of illness. Out of the 761 antibiotic use episodes, 659 (86.6%) were used inappropriately. Paying for healthcare without health insurance (Odds Ratio (OR): 2.10, 95% CI: 1.1–7.4, p-value: 0.026), not seeking healthcare from health centers (OR: 2.4, 95% CI: 1.2–5.0, p-value: 0.018), or pharmacies (OR: 4.6, 95% CI: 1.7–13.0, p-value: 0.003) were significantly associated with inappropriate antibiotic use. Socio-demographic characteristics were not significantly associated with inappropriate antibiotic use. However, the qualitative study described the influence of cost of medicines on inappropriate antibiotic use. It also revealed that antibiotic users with low socioeconomic status purchased antibiotics in installments which, could facilitate inappropriate use. Conclusion: Inappropriate antibiotic use was high and influenced by out-of-pocket payment for healthcare, seeking healthcare outside health centers, pharmacies, and buying antibiotics in installments due to cost. To improve appropriate antibiotic use, there is the need for ministry of health and healthcare agencies in Ghana to enhance healthcare access and healthcare insurance, and to provide affordable antibiotics.